Effect of hot deformation and crystallographic texture on toughness anisotropy and fracture behavior of Nb+V microalloyed API X70 steel. (March 2019) - Das Bakshi, S.; Dhande, T.; Javed, N.; Sasidhar, K.N.; Sharma, V.; Mukherjee, M.; Ghosh, B.; Mahashabde, V.V.
Abstract: The Charpy impact toughness (CVN) properties of a Nb + V microalloyed X70 steel of YS∼ 540 MPa was studied at various angles with respect to the rolling direction. The microstructure of the steel was characterised using light optical microscope, scanning electron microscope (SEM) and the transformation textures were evaluated from the orientation distribution function (ODF) measured from the electron back-scattered diffraction (EBSD) experiments. The skeleton lines, showing intensity distribution, f ( g ), of the fcc-to-bcc transformation texture, namely the α -fiber (<110> ∥ RD), the γ -fiber (<111> ∥ ND) and ε -fiber (<110> ∥ TD) are considered to explain the observed behavior in mechanical properties. The major components like, {112}<110>, {113}<110>, {332}<113>, {111}<112> and {111}<110>, their relative intensity distribution, are found to act in a complex manner towards controlling the mechanical behavior during impact and tensile testing. It has been observed that, the type and extent of delamination normally observed in broken Charpy specimens, which is commonly believed to be more dependent on the banding of 2nd phases in the microstructure, is found to be controlled by crystallographic texture, mostly clustering of {100} grains in the primary and secondary cleavage planes. Highlights: The extent of hot deformation below Tnr is pivotal in strengthening γ-fiber. Percentages {100}α grains and γ-fiber controls the mode of fracture. Two-dimensional banding of 2nd phases do not induce anisotropy or delamination. Delamination is caused by clustering of {100}α grains in the fissure plane. Crystallographic texture of hot band structure can alone introduce anisotropy.